Perencanaan SI pada Website Alat Kopi Gaharu Menggunakan Analisis SWOT dan CSF - Rafli, Muhammad; Sihombing, Karen Michelle; Handayani, Titis (Computer Science and Information Technology, 2025)
The utilization of information systems and information technology (IS/IT) by MSMEs is still not optimal, especially in supporting website-based marketing and sales. UMKM Gaharu Coffee Tools faces problems such as limited website features, less-than-optimal access speed, and the lack of integration between the ordering and payment systems, which impacts operational effectiveness and business competitiveness. This research aims to design an SI/IT strategic plan for the Gaharu Coffee Tools website to enhance business competitiveness. The research methods used include interviews and observations, which were analyzed using the SWAT and Critical Success Factors (CSF) methods. The results of the SWAT analysis show a difference of 1.38 between strengths and weaknesses and a difference of 1.10 between opportunities and threats, placing the website in the aggressive (SO) quadrant. The CSF analysis yielded three main priorities: capitalizing on the trend of home brewing, expanding the online market internationally, and managing a structured product catalog. In conclusion, targeted website development aligned with SI/IT priorities has the potential to enhance user experience, expand market reach, and sustainably strengthen the competitiveness of MSMEs.